2020
DOI: 10.12659/msm.928109
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Masseter Muscle Hardness of Stroke Patients Using the MyotonPRO Apparatus: Intra- and Inter-Rater Reliability and Its Correlation with Masticatory Performance

Abstract: Background Chewing dysfunction is one of the most common serious complications after a stroke. It may be influenced by the hardness of the masseter muscle and masticatory performance; however, the association between these 2 factors is not explicit. Thus, it is meaningful to explore the functional status of the masseter muscle among stroke patients. The main objectives of this study were to examine the intra- and inter-rater reliability of the MyotonPRO apparatus in measuring masseter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…Frequency indicated the muscle ability to resist external force of passive stretching. The higher the value the greater the muscle tone [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Frequency indicated the muscle ability to resist external force of passive stretching. The higher the value the greater the muscle tone [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the MyotonPro©, a manual device designed to assess MMPs, has provided reliable data in clinical settings [38]. In fact, the determination of MMPs has been successfully applied in assessing healthy subjects and athletes, patients with stroke, scoliosis, Parkinson's, chronic low back pain (cLBP), and cervical dystonia, among others [32,[39][40][41][42]. In spinal pain research, increases in tone and stiffness and decreases in the elasticity of the lumbar paraspinal muscles have been detected for axSpA and cLBP with the Myoton-Pro© [6,38,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1034 studies were identified in the search strategy, of which 16 were included in the systematic review [3,4,7,12,13,[19][20][21][22][23][24][25][26][27][28][29] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%